A perfect time for pandas - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series. Merlin missions, 2017)
Magically transported to southwest China to find the final object needed to break the spell on the wizard Merlin's beloved penguin, Jack and Annie take a side trip to the world's largest giant panda reserve.